Prevalence of Type 2 Diabetes Mellitus among Hypertensive Patients Attending in A Tertiary Level Hospital in Bangladesh - Haque, Amdadul; Hasan, Mahmud Javed; Ahmed, Tofayel Uddin; Ali, Md Yunus (Community Based Medical Journal, 2025)
This cross-sectional, descriptive study was conducted in the Department of Cardiology of Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh, between January and June of 2023, among the hypertensive patients to estimate the prevalence of type 2 diabetes mellitus and pre-diabetes (PD). A total of 93 patients with hypertension were purposively selected. Previously diagnosed diabetic patients were excluded from the study. Sociodemographic data were collected by face-to-face interview by using a pre-tested questionnaire. Fasting blood glucose and 2 hours after 75 gm glucose load were estimated by auto analyzer. Age, gender, weight and height and blood pressure were estimated. Body mass index (BMI) was estimated from body weight and height of the patients. Overall, DM was 21.5% and PD was 10.8% (IFG 1.1%, IGT 9.7%) evident in this study. Male showed higher prevalence of type 2 diabetes compare to female. Sex, age, occupation, education, sedentary lifestyle, increase frequency of rice eating showed no statistical significance with DM. All stages of hypertension, middle class economic status, overweight, depressives, family history of diabetes and smoking showed positive association with diabetes. Hypertension and PD showed no significant association. CBMJ 2025 July: vol. 14 no. 02 P:121-125